Linking savings behavior, confidence and individual feedback: a field experiment in Ethiopia - Avdeenko, Alexandra; Bohne, Albrecht; Frölich, Markus (Discussion paper, 2019)
In this paper we investigate behavioral constraints to savings among smallholder farmers in rural Ethiopia. Increasing savings by overcoming such behavioral constraints has been documented to have positive effects on various outcomes such as health, education, and agricultural investments. We causally identify a strong increase in savings to a soft commitment device in the form of a moneybox with a regular savings plan. In our randomized field experiment, we also provide personalized feedback consisting of recommendations to self-set saving goals. These recommendations trigger increases in savings of up to 36 percent. In a detailed analysis of the behavioral characteristics driving these results, we find a strong and robust link between financial confidence and savings behavior. In particular, the savings of underconfident individuals are less than 2/3 of the savings of overconfident individuals - an association stronger than other behavioral traits such as risk-lovingness and present-biasedness. Remarkably, the effect of our personalized feedback is particularly strong for underconfident individuals. We discuss possible underlying mechanisms, rule out a set of alternative behavioral explanations, and address crowding-out behavior into other forms of saving.
Keywords: Graue Literatur